Assessing Youth-Appealing Content in Alcohol Advertisements: Application of a Content Appealing to Youth (CAY) Index. Issue 2 (1st February 2018) - Padon, Alisa A.; Rimal, Rajiv N.; DeJong, William; Siegel, Michael; Jernigan, David
ABSTRACT: Underage drinking is a serious public health problem in the United States, and youth exposure to alcohol advertising has been indicated as a possible contributing factor. Although a number of studies have identified advertising content features that youth find appealing, a key limitation of this research is the absence of a broader tool to examine those features, especially those used by alcohol brands that are popular with underage drinkers. We created an index of content elements found in the research literature to be appealing to youth, and then used this index in a content analysis to identify the degree to which youth-appealing content appeared in a sample of alcohol ads that aired on television shows popular among youth. Finally, using bivariate analysis, we tested the relationship between alcohol brands' use of this content and the popularity of those brands among youth. We found that many of the ads featured youth-appealing content, and that the ads for the alcohol brands most popular among youth had more youth-appealing content than the less popular brands.